Balancing the Scales: Using Gender Impact Assessment in Hydropower Development - Australian Aid; CGIAR Challenge Program on Water and Food; Oxfam Australia (Oxfam, 2013)
Balancing the Scales in a manual designed to help planners and decision makers identify, understand, predict and respond to gender differences, opportunities and needs. The guide includes questions for staff involved in developing and managing projects and plans. The manual also helps companies consider their corporate practices beyond the project level, especially their operational policies and their project management frameworks through a lens of advancing gender equality and women’s rights.